AGE AND GROWTH OF THE SCAD DECAPTERUS DAYI WAKIYA - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Decapteiiix dayi Wakiya attains a length of 150 mm in the first year and 184 mm by 19 months at Vizhinjam. Maximum growth of 30 mm and 20 mm was noticed during the first and second months, respectively. Though many broods enter into the fishery in the same year, those bom in April manifest strongly in the fishery than the earlier and later ones. The younger broods tend to catch up the older ones by faster growth and form a unimodal group at the size of 120-129 mm, and are found as a distinct unimodal size class then onwards